Controlling vector-borne health issues and in-vitro effects of Nanoemulsion of essential Oils: A Review - Pal, Anupam Kumar; Sharma, Nisha (Asian Journal of Pharmaceutical Research and Development, 2020)
Controlling the parasitic and infectious diseases is a permanent health issue worldwide, requiring innovative methods for the prevention & treatment of illness triggered by parasites. Controlling vector and its intermediate hosts is an effective method for anticipation of human and animal’s diseases. It is essential to have bioactive components that act competently on the agents which produce the illnesses. Synthetic agents have strong surplus effects in humans & other animals, and they cause biological toxicity, affecting animals, plants and disturbing the local environment. Many studies have reported the effect of the Essential Oils (EOs). Essential Oils extracted from the medicinal plants are generally used as insect repellents worldwide. They are very safe and favorable to the environment with minimum ill-effects on animals and public health. It helps to control the vectors and also applicable against pathogens. Commonly Essential Oils easily degrade and cause less environmental pollution. Problems associated to solubility as well as stability lead to the improvement of effective carriers for formulations containing Essential Oils that is nanoemulsion. Nanoemulsion is a colloidal dispersion system, thermodynamically stable, prepared by two different non-miscible liquids assorted with emulsifying agents such as surfactants and co-surfactants, to form a single phase. Nanoemulsion a novel drug delivery system can be formulated by using two different techniques, the persuasion technique and the brute force technique. This review describes some studies accomplished with nanoemulsions as carriers of Essential Oils that have repellent, larvicidal, acaricidal, insecticidal and antiparasitic activities. Thus it can be used as substitutes in the vector control of parasitic and communicable diseases. Keywords: Nanoemulsion; essential oils; vector control; infectious diseases, insecticidal.